Treatment strategies and survival outcomes in older women with breast cancer: a comparative study between the FOCUS cohort and Nottingham cohort - Schuil, Hugo; Derks, Marloes; Liefers, Gerrit-Jan; Portielje, Johanneke; van de Velde, Cornelis; Syed, Binafsha; Green, Andrew; Ellis, Ian; Cheung, Kwok-Leung; Bastiaannet, Esther (Elsevier, 2018)
Objective: Clinical trials investigating breast cancer treatment often exclude or misrepresent older adults. This study compares treatment patterns and survival of older women diagnosed with breast cancer between a Dutch and a British observational cohort. Materials and Methods: Women aged 70 years and older diagnosed with breast cancer after 1990 with a T0-T2 tumor stage and no evidence of metastatic disease were included from a population-based cohort in the Netherlands and a British hospital-based cohort in Nottingham. Main outcomes were proportions of local and systemic treatment, ten-year overall survival and ten-year relative survival for each cohort. Results: 1439 patients from Nottingham and 2180 patients from the Netherlands were included. Median follow-up was 12.4 years (IQR 11.0–14.0) in the FOCUS cohort and 6.4 years (IQR 6.2–6.8) in the Nottingham cohort. British patients were more likely to receive primary endocrine therapy (50.0% vs 7.5%, P < 0.001), and less likely to be managed with mastectomy or breast-conserving surgery (47.8% vs 90.5%, P < 0.001). Ten-years overall survival was 39.4% (95% CI 37.4–41.6%) in the FOCUS cohort and 34.3% (95% CI 30.7–38.3) in the Nottingham cohort (adjusted HR 0.97, 95% CI 0.87–1.08, P = 0.559). Ten-year relative survival was 82.5% (95% CI 75.6–90.1) in the FOCUS cohort and 77.6% (95% CI 66.4–90.7) in the Nottingham cohort (adjusted relative excess risk 1.67, 95% CI 1.21–2.29, P = 0.002). Conclusion: Patients in the Nottingham cohort were more likely to receive primary endocrine therapy and had worse relative survival compared to the Dutch cohort. These findings encourage further research to equalize survival rates of breast cancer throughout Europe.